(untitled) (International Seven Journal of Multidisciplinary, 2024)
Breastfeeding is a fundamental practice for a baby’s health and proper development, offering a number of short- and long-term benefits for the baby and the mother. This natural form of feeding provides all the essential nutrients a baby needs in the first 6 months of life, promoting proper, healthy growth and strengthening the newborn’s immune system. In nutritional terms, breast milk is a complete source of proteins, fats, carbohydrates and vitamins. Breastfeeding provides a deep emotional connection between mother and child, allowing the release of feel-good hormones, promoting an emotional bond and a sense of security and tranquillity for the baby. For mothers, breastfeeding also brings numerous benefits. The release of oxytocin during breastfeeding helps to reduce postpartum bleeding and increases contraction of the uterus, aiding postpartum recovery and preventing hemorrhage. Breastfeeding can help with post-pregnancy weight loss and reduce the risk of developing breast and ovarian cancer. The (WHO) and (UNICEF) recommend exclusive breastfeeding for the first 6 months of a baby’s life, followed by the gradual introduction of complementary foods up to the age of two. However, despite the numerous benefits, many women face challenges to breastfeeding, including lack of support, returning to work and lack of information. It is therefore crucial to promote policies that support breastfeeding, such as paid maternity leave, breastfeeding-friendly workplaces and education programs for pregnant women and health professionals.